Pengaruh Pemanfaatan Teknologi Informasi Terhadap Minat Belajar IPA Siswa di SDN Ajung 3 Kelas 5 - I Ketut Mahardika; Firdha Yusmar; Rizka Elan Fadilah; Amelia Fiska Fajar Cahyani; Febi Lusiana Marta; Aulia Salsabila (Peneliti.net, 2022)
Technology is the application of behavioral and natural sciences and other knowledge in a systematic way to solve human problems. Technology that develops rapidly from time to time makes technology itself an important part of advancing a school. In the world of education technology is something that is very much needed. This technology is expected to be able to make the world of education in Indonesia able to compete with other developing countries. But on the other hand, these developments are not necessarily in accordance with the wishes or ideals of the nation. There are various impacts caused by technological developments. This research aims to determine the various impacts of technological developments on children's development. The research method used in this study is to find data by observing the object of observation ,as well as by looking for data sources from various literatures such as journals, books and the internet.